Lake season - Hunter, Denise, 1968- (Hunter, Denise, 1968- Bluebell Inn romance., 2019)
When their parents die in a tragic accident, Molly Bennett and her siblings pull together to fulfill their parents<U+2019> dream of turning their historic Bluebell, North Carolina, home back into an inn. Staying in town would be temporary<U+2014>three years at most<U+2014>then they plan to sell the inn, and Molly can get back to chasing her own dreams. Adam Bradford (aka bestselling author Nathaniel Quinn) is a reclusive novelist with a bad case of writer<U+2019>s block. Desperate for inspiration as his deadline approaches, he travels to the setting of his next book, a North Carolina lake town. There, he meets his muse, a young innkeeper who fancies herself in love with his alter ego. Molly and Adam strike up an instant friendship. When Molly finds a long-lost letter in the walls of her inn, she and Adam embark on a mission to find the star-crossed lovers and bring them the closure they deserve. But Adam has secrets he isn<U+2019>t ready to share. Past and present collide as truths surface, and Molly and Adam will have to decide if love is worth trusting.